Pitfalls and differential diagnosis on adrenal lesions: current concepts in CT/MR imaging: a narrative review - Reginelli, Alfonso (Gland Surg, 2020)
The purpose of this pictorial essay is to review the imaging findings of adrenal lesions. Adrenal lesions could be divided into functioning or non-functioning masses, primary or metastatic, and benign or malignant. Imaging techniques have undergone significant advances in recent years. The most significant objective of adrenal imaging is represented by the detection and, when possible, characterization of adrenal lesions in order to direct patient management correctly. The detection and management of adrenal lesions is based on cross-sectional imaging obtained with non-contrast CT (tumour density), contrast-enhanced CT including delayed washout (either absolute percentage washout or relative percentage one) and finally with MR chemical shift analysis (loss of signal intensity between in-phase and out-of-phase images including both qualitative and quantitative estimates of signal loss). The small incidental adrenal nodules are benign, in most of cases; some tumors such as lipid-rich adenoma and myelolipoma have characteristic features that can be diagnosed accurately in CT. On contrary, if the presenting contrast-enhanced CT shows an adrenal mass with uncertain or malignant morphologic features, particularly in patients with a known history of malignancy, further evaluations should be considered. The most significative implications for radiologists are represented by how to assess risk of malignancy on imaging and what follow-up to indicate if an adrenal incidentaloma is not surgically removed.